The American Jesuits : a history - Schroth, Raymond A. (New York University, 2007)
Choice Outstanding Academic Title for 2008. With infectious energy and a genuine gift for storytelling, Raymond A. Schroth recounts the history of Jesuits in the United States. The American Jesuits isn't simply a book for Catholics; it's for anyone who loves a well-told historical tale. For more than 450 years, Jesuit priests have traveled the globe out of a religious commitment to serve others. Their order, the Society of Jesus, is the largest religious order of men in the Catholic Church, with more than 20,000 members around the world and almost 3,000 in the United States. It is one of the m.